2022
DOI: 10.1097/icl.0000000000000934
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intense Pulsed Light Therapy in Dry Eye Disease Caused by Meibomian Gland Dysfunction: A Systematic Review and Meta-Analysis

Abstract: Supplemental Digital Content is Available in the Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 33 publications
(48 reference statements)
0
2
0
Order By: Relevance
“…Treatment usually consists of four consecutive sessions at three-week intervals, followed by adjuvant maintenance treatment every three to six months 5859. While a 2020 Cochrane review presented equivocal results,60 more recent clinical studies have demonstrated improvements in signs and symptoms of dry eye disease at one and three months after treatment completion,5861 with benefits lasting up to one year 5254. IPL therapy is considered safe and well tolerated.…”
Section: What Emerging Technologies Exist For Dry Eye Disease?mentioning
confidence: 99%
“…Treatment usually consists of four consecutive sessions at three-week intervals, followed by adjuvant maintenance treatment every three to six months 5859. While a 2020 Cochrane review presented equivocal results,60 more recent clinical studies have demonstrated improvements in signs and symptoms of dry eye disease at one and three months after treatment completion,5861 with benefits lasting up to one year 5254. IPL therapy is considered safe and well tolerated.…”
Section: What Emerging Technologies Exist For Dry Eye Disease?mentioning
confidence: 99%
“…Light and heat effects are common for treating MGD and other ocular surface diseases related to the eyelid. When conventional drug therapies fail to manage such diseases effectively under the eyelid tissue, targeted treatment and management of the affected tissues through light and heat penetration can be a viable alternative with promising results [ 20 ]. Intense pulsed light (IPL) uses a specific spectrum of visible light to generate heat that can reduce the inflammatory response and prevent the growth of new capillaries.…”
Section: Introductionmentioning
confidence: 99%